2019
DOI: 10.15517/rbt.v67is5.38934
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular differences between the Amphiamerican populations of Antillesoma (Sipuncula: Antillesomatidae), with the description of a new species

Abstract: Introduction: The sipunculans are a group of marine invertebrates that have been little studied in the tropical eastern Pacific (TEP). Antillesoma antillarum is a species belonging to the monospecific family Antillesomatidae, considered widely distributed in tropical and subtropical localities across the globe. Objective: The main objective of this work was to examine the morphological and molecular differences between specimens from both coasts of tropical America to clarify the taxonomy of this species. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 18 publications
1
12
0
1
Order By: Relevance
“…nigrescens from Israel, South Africa and, Broome, Australia, varies from 18% to 26% regarding Phascolosoma ( Phascolosoma ) varians from the Greater Caribbean. These values are similar to the results of Silva-Morales et al (2019) , where they found a genetic distance of 19% between Antillesoma antillarum (Greater Caribbean) and A. mexicanum (Southern Mexican Pacific). The present analysis reveals that Phascolosoma ( Phascolosoma ) nigrescens is a species complex resulting from the incipient morphological analysis.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…nigrescens from Israel, South Africa and, Broome, Australia, varies from 18% to 26% regarding Phascolosoma ( Phascolosoma ) varians from the Greater Caribbean. These values are similar to the results of Silva-Morales et al (2019) , where they found a genetic distance of 19% between Antillesoma antillarum (Greater Caribbean) and A. mexicanum (Southern Mexican Pacific). The present analysis reveals that Phascolosoma ( Phascolosoma ) nigrescens is a species complex resulting from the incipient morphological analysis.…”
Section: Resultssupporting
confidence: 90%
“…However, recent molecular analyses revealed potential taxonomic problems at the species level, where small morphological differences also were shown to correspond with distinct species, thus rejecting previously assumed wide distributions for some of those species ( Staton & Rice, 1999 ; Kawauchi & Giribet, 2010 ; Schulze et al, 2012 ; Kawauchi & Giribet, 2014 ; Johnson et al, 2016 ; Silva-Morales et al, 2019 ). Because of this, Kawauchi, Sharma & Giribet (2012) proposed to clarify the taxonomic status of each species through a meticulous case-by-case analysis, integrating molecular data while considering that some species names that are currently hidden under synonyms deserve to be restored.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…polymyotus become available, the name S. natans could be revalidated. This hypothesis is based on some recent papers where the use of molecular data has rejected the supposed wide distribution of some species (Staton & Rice 1999;Kawauchi & Giribet 2010, 2014Schulze et al 2012;Johnson et al 2016;Silva-Morales et al 2019).…”
Section: Morphological Remarksmentioning
confidence: 99%
“…Also, no identification key or updated list of the sipunculans from TEP exist. The presence of this group in the Southern Mexican Pacific (SMP) is completely unknown (Bastida-Zavala et al 2013); a single record of one new species in the SMP was made by Silva-Morales et al (2019). Therefore, the main objective of this work was to determine the composition of species of the phylum Sipuncula present in the study area.…”
Section: Introductionmentioning
confidence: 98%